A Comparative Study to Analyze the HBA1C and LIPID Profile in Type 2 Diabetic Patients with and without Diabetic Complications - Aamir Hussain, M Saqib Ur Rehman, Aneel Kapoor, Muhammad Ibrahim Mengal, Narindar Kumar, Hanozia Hassan, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the levels of HbA1c and lipid profile in type 2 diabetic patients with and without diabetic complications. Study design: A case-control study Place and Duration: This study was conducted at Bilawal Medical College for Boys at LUMHS Jamshoro Pakistan from September 2020 and September 2021 Methodology: The study sample size was n=140 type 2 diabetic patients. Thirty patients with DM 2 were used as controls, while 110 diabetic patients with problems such as neuropathy, retinopathy, and hypertension were used as cases. Clinicians diagnose based on the patient’s history, clinical examinations, and relevant investigations. The HbA1c level and lipid profile of diabetes individuals with problems were compared to diabetic patients without complications. Results: In this study, n=140 people with DM 2 were included. Males made up 55 % of the total, while females made up 45%. Furthermore, 65.4 % were under the age of 50 years. The average age was 45.544 ± 12.23 years. In this study, HbA1c was higher in DM 2 patients with chronic problems than diabetic patients without complications. Furthermore, the lipid profile of complicated patients was shown to be abnormal compared to the control group. Conclusion: In diabetic individuals, HbA1c levels should be kept within normal limits to avoid long-term consequences. It can also benefit diabetic patients who have an abnormal lipid profile